2021
DOI: 10.1113/jp281849
|View full text |Cite
|
Sign up to set email alerts
|

Premovement inhibition can protect motor actions from interference by response‐irrelevant sensory stimulation

Abstract: support-information-section).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 62 publications
(154 reference statements)
2
12
1
Order By: Relevance
“…With respect to the StartReact effect, shorter RTs were observed on LAS trials, and the same pattern of preparation‐level effects on RT and neural activation was present on both tone and LAS trials. Collectively, these results comment on the nature of movement preparation as (1) a quickly evolving process shaped by expectations about when the action is likely to be required (see also Churchland et al, 2006; Crammond & Kalaska, 2000; Elsayed et al, 2016; Ibanez et al, 2020; McInnes, Lipp, et al, 2021), and (2) a distributed process that also engages circuits beyond those involved in the execution of the motor action like the auditory cortex (Chen et al, 2006; Gale et al, 2021). The results also suggest that even the fastest reactions to LAS can be explained by a combination of established phenomena and that the existence of a separate subcortical pathway that bypasses the motor cortex is not necessary to explain the StartReact effect – at least for cortically mediated actions such as individual finger movements (Marinovic & Tresilian, 2016).…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…With respect to the StartReact effect, shorter RTs were observed on LAS trials, and the same pattern of preparation‐level effects on RT and neural activation was present on both tone and LAS trials. Collectively, these results comment on the nature of movement preparation as (1) a quickly evolving process shaped by expectations about when the action is likely to be required (see also Churchland et al, 2006; Crammond & Kalaska, 2000; Elsayed et al, 2016; Ibanez et al, 2020; McInnes, Lipp, et al, 2021), and (2) a distributed process that also engages circuits beyond those involved in the execution of the motor action like the auditory cortex (Chen et al, 2006; Gale et al, 2021). The results also suggest that even the fastest reactions to LAS can be explained by a combination of established phenomena and that the existence of a separate subcortical pathway that bypasses the motor cortex is not necessary to explain the StartReact effect – at least for cortically mediated actions such as individual finger movements (Marinovic & Tresilian, 2016).…”
Section: Discussionmentioning
confidence: 72%
“…Although the distinction between preparation and initiation does not meaningfully change our interpretation that preparation is associated with evolving and widespread changes in brain dynamics, the distinction between processes may be important in future studies considering more complex movements and high‐urgency situations – when actions might be initiated before movement preparation is complete. In that regard, we have recently reported that actions initiated with very short preparation times do not undergo the typical suppression of the corticospinal system (McInnes, Lipp, et al, 2021), a phenomenon observed for reaction time, anticipatory and self‐paced actions (Ibanez et al, 2020). We have proposed that preparatory suppression might be related to the protection of the motor action from interference (McInnes, Lipp, et al, 2021), so it would be interesting to investigate how the gradual increase in preparatory activity observed in our task relates to changes in corticospinal excitability.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…A well-documented phenomenon when humans engage in action preparation is preparatory suppression. Preparatory suppression reflects a period of CS suppression relative to baseline (at rest) that is observed approximately 250 ms to 100 ms prior to action initiation (Davranche et al, 2007; Duque et al, 2010; Duque & Ivry, 2009; Hannah et al, 2018; Hasbroucq et al, 1997, 1999; Ibáñez et al, 2020; Klein et al, 2016; Lebon et al, 2016; Marinovic et al, 2015; McInnes et al, 2021; Starr et al, 1988; Zaaroor et al, 2003). Previous research investigating the time course of this preparatory suppression in reactive, anticipatory, and self-timed actions, showed that this period of CS suppression is followed by a period of facilitation, and this was common to all three types of movements participants performed (Ibáñez et al, 2020).…”
Section: Introductionmentioning
confidence: 99%